Complete mitochondrial genome and phylogenetic analysis of Diaphania perspectalis - Shengquan Que; Ailin Yu; Yegou Tu; Caiyun Xiong; Xiaohua Liu (Mitochondrial DNA. Part B. Resources, 2019)
To explore the evolutionary relationships of Pyralidae, the complete mitochondrial genome of Diaphania perspectalis (Walker) was sequenced and annotated. The genome is found to be 15,232 bp in length and has a base composition of A (39.8%), G (7.7%), C (11.4%), and T (41.1%). Similar to other Pyralida species, it contains a typically conserved structure including 13 protein-coding genes, 2 rRNA genes, 1 control region (D-loop), and 22tRNA genes. The proportion of coding sequences with a total length of 11,433 bp is 75.06%, which encodes 3787 amino acids. Most of the protein-coding genes are initiated by typical ATN codons. Ten are terminated with TAA, whereas three genes, coxII and nad4, harbor incomplete termination codons of a single T. The lengths of 12S ribosomal RNA and 16S ribosomal RNA are 779 bp and 1338 bp, respectively. The length of control region is 317 bp, ranging from 14,916 bp to 15,232 bp. The complete mitochondrial genome sequence provided here would be useful for further understanding the evolution of ratite and conservation genetics of D. perspectalis.